The Effectiveness of Guided Reading and Reciprocal Teaching Techniques to Teach English for Information Technology Purposes to Differently Motivated Students - Kurniawan, Andreas Heri (Universitas Negeri Semarang, 2019)
This study intends to explain the effectiveness of Guided Reading Technique (GRT) and Reciprocal Teaching Technique (RTT) as a means of teaching English for IT purposesto differently motivated students. Based on the question, this research intends to show the effectiveness of GRT to teach highly motivated students, the effectiveness of RTT to teach lowly motivated students, and the difference between the groups of students before and after being taught using GRT and RTT. This quasi-experimental study uses 2X2 factorial design. Two groups of students are located in their regular setting, taught by relatively similar quality teachers, using similar teaching-learning facilities except teaching techniques which are made different. The first group was taught using GRT, while the second was taught using RTT. Prior to the experiment proper, pre-test was administered to the two groups. The purpose on this test was to make sure that their competence in English for IT purposes was equal. The students were also asked to fill in a questionnaire to measure their levels of motivation. The results of the experiment show that (1) both techniques provide the same results when applied to highly motivated students; (2) both techniques provide similar results when applied to lowly motivated students; (3) there is a significant difference among the groups of students before and after being taught using GRT compared to RTT